A theory of supplier network-based innovation value. Issue 3 (June 2017) - Yan, Tingting; Yang, Sophie; Dooley, Kevin
Abstract: To understand how a supplier helps a buying company create value through innovations, studies have focused on a supplier's internal resources or its relationship with a buying company. Building upon this body of literature, we develop a theory of supplier network-based innovation value in this conceptual paper. This theory explains how a supplier's upstream and downstream value network can be a source of competitive advantage for a buying company. Specifically, it proposes that the levels and types of supplier innovation value is contingent on the configuration of a dual-ego value network, characterized by the locus and degree of buyer-supplier structural equivalence. This theory also explains how a supplier's ties with a buying firm's competitors can pose both opportunity and risk to buying company innovation. This theory contributes to the literature by showing when "seemingly undesirable" suppliers, due to a lack of technical capability or strong relationship with a buying company, might still be valuable to a buying company's innovation. Highlights: This paper provides a network-based explanation for how buying firms can extract innovation value from their suppliers' value networks. This study develops propositions concerning how different types of structural equivalence, a social network concept, between the buyer's and supplier's value networks can lead to different types of supplier innovation value. The theory also explains how a supplier's ties with a buying firm's competitors can pose both opportunity and risk to buyer innovation.